PENDIDIKAN MITIGASI BENCANA GEMPA BUMI KEPADA SISWA KATEKISASI DI SEKTOR CALVARY JEMAAT GPM REHOBOTH - Huwae, Laury Marcia Chara; Hukubun, Ronald Darlly; Hukubun, Wiwien Gaby (Universitas Pattimura, 2022)
Disaster mitigation is an effort that can be done to prevent casualties and minimize losses, this is in line with the condition of Maluku which is prone to earthquakes. This PKM aims to provide knowledge and understanding of earthquake disaster mitigation. The service method is presented in the form of providing material, discussion and evaluation. It is hoped that the targeted catechism students (partners) can become “agents of change” in sharing information and knowledge with the general public about the importance of disaster emergency preparedness